Towards social stability and democratic governance in Central Eurasia : challenges to regional security - Morozova, Irina Y. (Irina Yurievna) (NATO science series. Science and technology policy, 2005)
Provides the contributors' views on the socio-political challenges confronting the nine Central Eurasian states. This book presents scientific discussions on the historical development of Central Eurasia and its sociocultural legacies; Soviet and contemporary state organisation, social transformation and communal structures; and more.